Distance‐dependent V2I wireless channel characteristics and performance in 5G small cell based on measurements. Issue 20 (15th December 2020) - Li, Changzhen; Wang, Shoufeng; Yu, Junyi; Chen, Wei; Yang, Kun
Abstract : The maturity of 5G technology has promoted the rapid development of vehicular communications and intelligent transportation systems. As an important part of vehicular communications, vehicle‐to‐infrastructure (V2I) is used for the huge data transmission between vehicles and roadside units. Aiming to analyse the V2I wireless channel distance‐dependent characteristics, this study presents two 5.9 GHz measurements in urban and suburban propagation scenarios. The distance‐based amplitude distribution, delay and Doppler spreads, path loss and shadowing are extracted from the raw data. It is noted that the characteristics of V2I wireless channel vary with the distance between the transmitter and receiver. Rich multi‐path components in the urban area will make more influence than that in the suburban area. Similar with the 5G pico‐cell, the coverage distance, signal‐to‐noise ratio and channel capacity are calculated from the measurement data. The proposed results indicate that the coverage ranges of urban and suburban V2I wireless communication are about 250.3 and 80.04 m when the average power received from a single reference signal is − 85 dB . Rich reflection effect from surroundings in the urban propagation scenario will lead to a faster attenuation of wireless signal. The proposed results can provide a meaningful reference for future research of 5G vehicular communications.